Rangga Raja di Titik Nol: Perjalanan Psikologis dalam Novel 0 MDPL Karya Nurwina Sari - Intan Khoirotul Awaliya; Nori Aggraini (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to conduct an in-depth analysis of the psychological journey of the character Rangga Raja in the novel 0 MDPL by Nurwina Sari. The main focus of the study is to identify the inner conflicts experienced by the protagonist as well as the dynamics of the personality structure consisting of the Id, Ego, and Superego that shape his psychological development throughout the storyline. This research employs a literary psychology approach using a qualitative descriptive method, conducted through a literature review and document analysis of the novel text as the primary data source. The findings indicate that Rangga Raja experiences complex emotional conflicts resulting from past trauma, experiences of loss, and failures in romantic relationships. These conditions are reflected through the tensions and interactions between the Id, Ego, and Superego within himself. The process toward the “zero point” (0 MDPL) is interpreted as a symbol of an identity crisis phase as well as a stage of self-reconstruction, in which the protagonist undergoes processes of reflection, self-acceptance, and openness to change. In addition, Rangga’s interactions with other characters, such as Andini, La Nina, and Nadia G. Sahara, play an important role in his psychological recovery and healing process. This study confirms that the novel 0 MDPL represents a profound reflection on human psychological dynamics, the search for identity, and the gradual process of inner healing.